Zinc Oxide Quantum Dots as Efficient Electron Mediator for Ultrasensitive and Selective Electrochemical Sensing of Mercury. (1st October 2015) - Bhanjana, Gaurav; Dilbaghi, Neeraj; Kumar, Rajeev; Kumar, Sandeep
Graphical abstract: Highlights: Synthesis and characterization of ZnO quantum dots. Fabrication of ZnO/Nafion/Au electrode. LSV & Chronoamperometricsensing of mercury ionsusingfabricatedelectrode. Real sample analysis using modified ZnO/Nafion/Au electrode. Abstract: Heavy metals especially mercury represents one of the most hazardous substances that need to be estimated and monitored. Even though various qualitative and quantitative methods have been used to classify or eliminate mercury, but most of the processes entailed complex routes and refined instrumentations. Here, in this work, we developed a highly efficient, ultrasensitive and selective electrochemical sensor for the trace level measurement of mercury on zinc oxide quantum dots by using Linear Sweep Voltammetry (LSV). The prepared nanosensor possesses a very high detection limit of 5 ppb with sensitivity of 4.6 μA cm -2 ppm -1 in response time of <2s. The fabricated sensor is reproducible and stable upto three months. Considerably this is the lowest detection limit attained for the determination of mercury amongst other reported electrochemical sensors for mercury. In addition, the selectively of sensor towards mercury is very high even in the presence of other common interfering ions. The practicability of the current sensor has also been measured in real environmental samples with good recoveries and with consistent results as verified with other standard technique.